Angiotensin (ang) 1-7 inhibits ang II-induced atrial fibrosis through regulating the interaction of proto-oncogene tyrosine-protein kinase Src (c-Src) and Src homology region 2 domain-containing phosphatase-1 (SHP-1)). Issue 2 (20th December 2021) - Lu, Li; Cao, Li; Liu, Yihao; Chen, Yunlin; Fan, Jinqi; Yin, Yuehui
ABSTRACT: To verify whether Ang-(1-7) produces an antagonistic effect on Ang II-mediated atrial remodeling. Ang II–induced HL-1 cell model and a rat model of Ang II–induced atrial remodeling were constructed and intervened with Ang II Ang-(1-7), AngII +Ang-(1-7), Ang II+ c-Src specific inhibitor (SU6656), and Ang II + Ang-(1-7) + SSG (SHP-1/2 specific inhibitor, stibogluconate), respectively. The systolic blood pressure of the rat caudal artery was detected. And trial fibrosis was detected by Picrosirius red staining and Masson's trichrome staining. Expressions of transforming growth factor-β (TGF-β), tissue inhibitor of metalloproteinases 1 (TIMP1), Matrix metalloproteinase 2 (MMP-2), connective tissue growth factor (CTGF), galectin-3, α-smooth muscle actin (α-SMA), and collagen I/III were subjected to qPCR and western blot. Furthermore, SHP-1 binding to c-Src was verified by co-immunoprecipitation (Co-IP). Results showed that the expressions of TGF-β, TIMP1, MMP-2, CTGF, α-SMA, galectin-3, and collagen I were increased markedly in the Ang II intervention group, and the expressions of p-ERK1/2, p-Akt, and p-p38MAPK were also increased dramatically. Ang-(1-7) or SU6656 addition could inhibit the action of Ang II factor, thereby minimizing the expressions of the previously described genes and proteins. Simultaneously, SSG supplement reversed the antagonistic effect of Ang-(1-7) on Ang II, and the latter elevated the blood pressure and induced atrial fibrosis in rats. Ang-(1-7) could reverse the changes related to Ang II–induced atrial fibrosis in rats. In conclusion, Ang-(1-7) antagonized Ang II–induced atrial remodeling by regulating SHP-1 and c-Src, thereby affecting the MAPKs/Akt signaling pathway.